Efetividade da equoterapia no enfrentamento de problemas de comportamento em crianças - Flôres, Fabrine Niederauer (2020)
The present research aimed to investigate the effects of an intervention in hippotherapy with children with behavioral problems through a randomized clinical study with a control group. The study sample consisted of 28 children (male = 14; female = 14) aged 6 to 9 years (M = 7.68, SD = 1.02) from southern Brazil participated in the study, 15 (male = 8) in the intervention group (M = 7.67 years, SD = 1.17) and 13 (male = 6) waiting list controls (M = 7.69 years, SD = 0.85), 53.6% studied in public education, 28 guardians (n = 26 parents and n = 2 grandparents) and 22 teachers. The children showed behavioral problems identified in the SDQ test in the teachers' view. The study met the ethical precepts in research with human beings, being approved by the Ethics Committee in research with human beings at the Federal University of Santa Maria (UFSM). The instruments used for data collection were: semi-structured interviews containing sociodemographic data, questions about children's social behavior and skills, Skills and Difficulties Questionnaire - SDQ, Social Skills Inventory, Behavior Problems and Academic Competence for children - SSRS, Script Interview of Social Educational Parenting Skills - RE-HSEP, School Performance Test - TDE II and also a measure of satisfaction. The instruments were applied individually with parents and children in the riding therapy center, as well as in schools, with previously scheduled times. The teachers responded to the tests individually and with self-completion in the school environment. The interventions by means of the horse were carried out at the hippotherapy center partner of the research with a weekly session, individually for the 15 children of the IG, lasting 40 minutes each, totaling 16 sessions. After the end of the intervention, the tests were applied again (post-test) in both groups with all participants. An intra-group analysis was performed in the IG to verify the statistical difference of the following measures: pre- vs. post-intervention, as well as between groups (post-test moments of GI versus GC. Analyzes with t-test for paired samples and respective Wilcoxon were performed to identify pre-post-intervention effects in the hippotherapy group. Statistically significant differences were identified in the parents' perception for improvement in general behavioral problems, internalizing and externalizing, social skills, and in the subscales self-control, social resourcefulness, total difficulties, conduct problems, hyperactivity, emotional symptoms and problems with children's colleagues after participating in the intervention. As for the teachers' perception, there was an improvement in the total difficulties and cooperation / affection of the children, as well as better results in post-intervention writing and arithmetic. There were no significant differences between baseline and post-intervention scores for the other variables evaluated. The Mann-Whitney test revealed improvements in the total of difficulties, conduct problems, responsibility, writing and arithmetic in the intervention group compared to the post-intervention controls, in the teachers' perception. After the intervention, improvements in the results of the variables evaluated in this sample of children were identified, reducing behavioral problems and improving social skills and school performance. It was concluded that children who underwent hippotherapy showed improvements, showing that the intervention is promising. It is suggested to promote scientific studies with methodological rigor to strengthen hippotherapy as an evidence-based treatment in the field of Psychology.